2022
DOI: 10.3390/nu14214700
|View full text |Cite
|
Sign up to set email alerts
|

Potential Allergenicity Response to Moringa oleifera Leaf Proteins in BALB/c Mice

Abstract: The reported association of Moringa oleifera seeds and allergic disease clinically resembling occupational asthma in cosmetic manufacturing workers has resultedin the need to identify such components in the manufacturing process. However, Moringa oleifera leaves from the same plant, an important food ingredient, have limited immunotoxicity data. This study aimed to determine if Moringa oleifera leafproteins (MLP) can elicit allergic responses in BALB/c mice. The BALB/c mice were sensitized twice and challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…However, it should be noted that some individuals may be allergic to M. oleifera leaves. Previous studies have investigated M. oleifera leaf allergens [ 6 , 7 , 8 ], but the mechanism through which Mo-Pr or M. oleifera leaf allergen causes allergies as well as its effect on DCs remain unclear. Food allergy is a significant public health issue worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that some individuals may be allergic to M. oleifera leaves. Previous studies have investigated M. oleifera leaf allergens [ 6 , 7 , 8 ], but the mechanism through which Mo-Pr or M. oleifera leaf allergen causes allergies as well as its effect on DCs remain unclear. Food allergy is a significant public health issue worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on M. oleifera leaf allergens. Jie Zhang et al successfully sensitized BALB/c mice to M. oleifera leaf protein through oral administration [ 6 ]. Giovanni D’Auria et al identified potential M. oleifera leaf allergens, including morintides and nsLTP, through proteomic analysis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…M. oleiferaleaves are the leafy part of the same plant and are an economic substitute for staple foods. A potential allergenic response to Moringa oleifera leaf proteins (Mo-Pr) has been reported to cause oral allergy in BALB/c mice [11].…”
Section: Introductionmentioning
confidence: 99%